2012
DOI: 10.3390/rel3030588
|View full text |Cite
|
Sign up to set email alerts
|

The English Version of the Multidimensional Inventory for Religious/Spiritual Well-Being (MI-RSWB-E): First Results from British College Students

Abstract: Abstract:In recent years there has been a steadily growing interest of religious/spiritual issues in several areas of psychology; a variety of reliable and valid means of assessing the different facets of religiosity/spirituality have been developed. However, there is still some need for multidimensional approaches. With respect to the positive experience with the German version of the Multidimensional Inventory for Religious/Spiritual Well-Being, we developed an English version of this scale (MI-RSWB-E) in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 15 publications
5
23
3
Order By: Relevance
“…In the previous research, Cronbach’s α was found to be at least 0.68 for all the sub-scales and 0.89 for the RSWB total score [ 23 ]. A full item list for the English version of the scale together with a short manual can be retrieved from Unterrainer et al [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the previous research, Cronbach’s α was found to be at least 0.68 for all the sub-scales and 0.89 for the RSWB total score [ 23 ]. A full item list for the English version of the scale together with a short manual can be retrieved from Unterrainer et al [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between spirituality and physical health has been studied in previous research mostly from two perspectives: Either in connection with specific chronic diseases [12,13] or in connection with subjective health [11]. Attention has also been given to the connection between spirituality and different aspects of mental health among university and college students [14,15], secondary school students [16], and children [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this research has demonstrated that high levels of SWB are positively associated with enhanced life satisfaction (Yazdi Moghadam et al 2009 ). Thus, given the importance of SWB toward physical and psychological health, there is a need for the psychometric evaluation of measurements evaluating SWB (e.g., the Sense of Well-Being Scale [SWBS]) (Unterrainer et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%